Neuroscience: a more dynamic view of the social brain. - Sallet, J; Mars, R; Rushworth, M (2012)
Information relevant for social interactions is thought to be processed in specific neural circuits. Recent studies shed new light on how that social information is encoded and processed by different brain areas.